Geir Otto Holmås, Prayer and Vindication in Luke-Acts. The Theme of Prayer within the Context of the Legitimating and Edifying Objective of the Lukan Narrative (Library of New Testament Studies 433; New York – London: T&T Clark, 2011) - Mielcarek, Krzysztof (The Biblical Annals, 2017)
Book review: Geir Otto Holmås, Prayer and Vindication in Luke-Acts. The Theme of Prayer within the Context of the Legitimating and Edifying Objective of the Lukan Narrative (Library of New Testament Studies 433; New York – London: T&T Clark, 2011). Pp. xvi-300. USD 103.60. ISBN 978-0-567-01756-7 (Hardback).